Strategi Perancangan UI/UX Aplikasi Mobile Untuk Mengoptimalkan Pengalaman Pengunjung Museum SMB II - Charoline Rafista; Dewi .; Felicia Carita; Tia Amelia; Anugerah Widi (MDP Student Conference, 2026)
Sultan Mahmud Badaruddin (SMB) II Museum is a historical icon of Palembang City; however, the limited availability of tour guides, interactive media, and digital interaction has resulted in a suboptimal visitor experience. This study aims to design the user interface (UI) and user experience (UX) of a mobile museum companion application using the Design Thinking method, which consists of the Empathize, Define, Ideate, Prototype, and Test stages. The main focus of the design is to create an intuitive self-guided tour experience to help visitors access historical information more easily and interactively. This study produces a prototype application named SriWarna, which is evaluated using the User Experience Questionnaire (UEQ). The prototype integrates local Palembang cultural elements into a modern digital interface. The evaluation results indicate that the proposed application design enhances visitor engagement and facilitates independent access to historical information. Nevertheless, the SriWarna application has the potential to be further refined in order to provide a more consistent and optimal user experience for all museum visitors.